Pola Komunikasi Antara Dosen Dengan Mahasiswa Dalam Upaya Meningkatkan Motivasi Belajar Mahasiswa Selama Kuliah Online di Era Covid-19 - Sri Rahadian Mukjizat Sakti (Jurnal Ilmiah Komunikasi (JIKOM) STIKOM IMA, 2023)
This research uses a qualitative descriptive design. The population of this study were lecturers and students at the University of Indonesia Maju. The informant selection technique used purposive sampling, including key informants for the Coordinator of the Bachelor of Communication Studies Study Program, and informants supporting lecturers and students. Collecting data using observation, interviews, documentation. The research data analysis technique is Milies and Huberman. The results of research on learning systems between lecturers and students at the University of Indonesia Maju use online systems such as Google Classroom, Zoom, Skype, Google Meet, and so on. This online learning system, is a pattern of communication relationships between lecturers and students who are still facing problems that are not easy because of the gap between what is expected and the results that can be achieved from the educational process. Joseph A. De Vito communication of wheel patterns, chain patterns, circle patterns, y patterns and overall patterns (All Channel). Application of communication patterns between lecturers and students, this should increase student motivation to learning, but the fact is that this communication pattern is still not going well, the impact can be a decrease in student learning motivation during online lectures.The conclusion in this study, the pattern of communication between lecturers and communication science students at the Indonesia Maju University in an effort to increase student learning motivation during online lectures, is still has not gone well. The suggestion for this research is that it is necessary to have the right communication strategy, related to the learning methods conveyed to students can be well understood and accepted. The target output of this research is in the form of research results published in nationally accredited journals. Organization Communication courses.